2010
DOI: 10.1007/s10608-010-9297-z
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Homework Compliance and Therapy Outcomes: An Updated Meta-Analysis

Abstract: The current study was an updated meta-analysis of manuscripts since the year 2000 examining the effects of homework compliance on treatment outcome. A total of 23 studies encompassing 2,183 subjects were included. Results indicated a significant relationship between homework compliance and treatment outcome suggesting a small to medium effect (r = .26; 95% CI = .19–.33). Moderator analyses were conducted to determine the differential effect size of homework on treatment outcome by target symptoms (e.g., depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
162
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(176 citation statements)
references
References 36 publications
12
162
1
1
Order By: Relevance
“…In a metaanalysis, Kazantzis, Whittington, and Dattilio (46 studies; n=1,072) [21] concluded that 62% of patients undergoing a therapy with homework improved significantly, whereas only 38% of patients undergoing a treatment without homework improved significantly. Mausbach, Moore, Roesch, Cardenas, and Patterson (23 studies; n=2,183) [22] reported similar results, showing a small to medium effect (r=0.26) of homework compliance on treatment outcome. Thus homework compliance can be viewed as a major process factor in treatment.…”
Section: Methods Study Objectives and Designmentioning
confidence: 70%
See 1 more Smart Citation
“…In a metaanalysis, Kazantzis, Whittington, and Dattilio (46 studies; n=1,072) [21] concluded that 62% of patients undergoing a therapy with homework improved significantly, whereas only 38% of patients undergoing a treatment without homework improved significantly. Mausbach, Moore, Roesch, Cardenas, and Patterson (23 studies; n=2,183) [22] reported similar results, showing a small to medium effect (r=0.26) of homework compliance on treatment outcome. Thus homework compliance can be viewed as a major process factor in treatment.…”
Section: Methods Study Objectives and Designmentioning
confidence: 70%
“…In this context, the operationalization of homework compliance plays an essential role. Although homework is an important part of cognitive behavioral therapy [57][58]21], metaanalyses clearly show that findings on the effect of homework depend strongly on how homework compliance is defined and measured [57,[21][22]. As this study implemented an improved methodology, using the mean score of homework compliance from the first five sessions, the results are based on a more representative estimator [32].…”
Section: Acta Psychopathologica Issn 2469-6676mentioning
confidence: 99%
“…However, many of these elements of the therapeutic interaction still lack focused assessment and empirical study. For example, while studies have considered the causal benefits of including homework in CBT , correlational adherence-outcome relations (Kazantzis et al 2016;Mausbach et al 2010), and session-by-session benefits associated with homework adherence (Conklin and Strunk 2015), more research is needed on the in-session therapist behaviors that can facilitate engagement Startup and Edmonds 1994;and see;Shaw et al 1999 for evidence of competence in structuring sessions as a predictor of outcomes). Similarly, existing measures may not fully capture the definition of collaboration in CBT (Kazantzis et al 2015;Tryon and Winograd 2011), the evidence for Socratic dialogue is just emerging (Braun et al 2014), and study of feedback processes has centered on symptom assessments (Knaup et al 2009;Lambert and Shimokawa 2011).…”
Section: In-session Processesmentioning
confidence: 99%
“…negative automatic thoughts, mood tracking) that do not necessarily require input from a therapist and are often covered in self-directed computerised CBT suggests that apps may in particular be a useful addition to low-intensity CBT. They may be particularly effective in facilitating engagement with CBT "homework" (which often requires recording thoughts and emotions, planning activities or tracking mood), which is a desirable outcome as regular engagement with such CBT exercises increases the effectiveness of therapy [50,51]. Moreover, the results show that apps have important advantages with regard to 'integration into practice': they are always at hand, are more private and discreet than paper worksheets, and they allow to easily share data with the therapist.…”
Section: Integration Into Different Therapeutic Practicesmentioning
confidence: 99%